Synthesis Of Light Colour Medium Chain Triglycerides From Palm Kernel Oil Products - Jamaludin, Radzuan (1999)

(untitled)
The synthesis of light colour medium chain triglycerides (MCTs) from medium chain fatty acids (MCF As) and glycerol was investigated in this study. The production of light colour medium chain triglycerides is tedious and consists of several purification steps. This causes an increase in production cost and its economic viability. In this study, homogeneous catalyst, homogeneous catalysts with an absorbent and heterogeneous catalyst were used in an effort to establish methods to minimise cost. Catalyst was used in order to reduce the reaction temperature, time and produce higher percentage conversion of MCTs, whereas absorbent helps in producing light colour MCTs. The results showed that the use of homogeneous catalyst reduced the temperature and time of the reaction with higher conversion rate of MCTs, but the product obtained was dark in colour. However, with the presence of absorbent, the colour of the product obtained improved tremendously to almost colourless.